4Dimensional XStrain Echocardiography assessment of Left Bundle Branch Cardiomyopathy in an elderly male : A case report - Mehrotra, Akhil; Mohammad Shaban; Ujala Shakya (International Journal of Medical Research and Review, 2024)
Left bundle branch block (LBBB) is generally associated with a poorer prognosis in comparison to normal intraventricular conduction. LBBB may be the first manifestation of a more diffuse myocardial disease. The typical surface ECG feature of LBBB is a prolongation of QRS above 0.11s in combination with a delay of the intrinsic deflection in leads V5 and V6 of more than 60 ms and no septal q waves in leads I, V5, and V6 due to the abnormal septal activation from right to left. LBBB may induce abnormalities in left ventricular performance due to abnormal asynchronous contraction patterns. Asynchronous electrical activation of the ventricles causes regional differences in workload which may lead to asymmetric hypertrophy and left ventricular dilatation, especially due to increased wall mass in late-activated regions, which may aggravate preexisting left ventricular pumping performance or even induce it.